If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -12 = 3 + -3x Reorder the terms: -12 + 2x = 3 + -3x Solving -12 + 2x = 3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -12 + 2x + 3x = 3 + -3x + 3x Combine like terms: 2x + 3x = 5x -12 + 5x = 3 + -3x + 3x Combine like terms: -3x + 3x = 0 -12 + 5x = 3 + 0 -12 + 5x = 3 Add '12' to each side of the equation. -12 + 12 + 5x = 3 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = 3 + 12 5x = 3 + 12 Combine like terms: 3 + 12 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| x=y^2+2y+4 | | 3(2x-5)=-9 | | (x+1)(x+1)=x^2-3 | | 7ab*a=36ab | | 2(x-1)-5(x+2)=10 | | 3(3+x)=7(2-X)+5 | | (2x+7)(5x-2)=0 | | (2x-1)*(-x^2+2x-3)=3 | | x^5=1.333 | | 0=4x^2-4x-3-y | | 7-2(10x+1)=25 | | 8x+2+3x+6=x+12 | | 7x+5+x-3+x=5 | | 3x-2(x+3)=9 | | 12=20x-18 | | 3(5x+10)+10=6x-(x+10) | | 12/30n=-38 | | 13x+11y+6z=42 | | 3x^3+x^2+75x+25=0 | | x^5-6*x^4+5*x^3=0 | | x^3-5*x^2+9*x+13=0 | | 160=5x+10x+4 | | 4(3x+1)=32 | | -20=-x-6x | | 5x+10y=350 | | (6y+5)-3+5y=5 | | x^2-(2b-1)x+(b^2-b-20)x=0 | | 42x=700 | | x^2+40x-48000=0 | | x^2+20x-48000=0 | | 3x+85=49 | | 4*x^2-2*x-12=0 |